Hubungan Dukungan Keluarga Terhadap Praktek Pemberian Makan Anak Usia Bawah Dua Tahun (12-23 Bulan) - Fauziah Nurlan; St. Aminah; Sakaria Anwar; Abd. Wahidin (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
This study aims to determine the relationship of family support with parenting practices in feeding practices to children under the age of two years (Baduta) in the working area center for health community of Binamu Kab Jeneponto. This type of research is observational analytic with cross sectional study approach. The sample used was mothers who have children aged 12-23 months, totaling 136 people out of 210 population. The sampling technique was done by simple random sampling and data were collected using a questionnaire. Hypothesis testing is done using the Chi Square testwith a significance value of 0.05, p<0.05. Statistical analysis using the SPSS 21 aplication. The results of data analysis showed that there was no relationship between family support toward the practice of feeding children under two years of age, p values 0.449 >0.005. This research requires further research that analyzes the nutritional status of children.